Design, Synthesis, and Photophysical and Biological Studies of Naphthalimide Bioconjugates for Medicinal and Materials Applications - Ramirez Lazaro, Laura (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2025)
This thesis presents significant advancements in the synthesis, characterization, and use of Naphthalimide (Nap) based biological relevant compounds for bioimaging and therapeutic applications. Extensive photophysical studies were conducted on each derivative, focusing on both aggregation-caused quenching (ACQ) and aggregation-induced emission (AIE) properties to assess their performance in various biological and physiological environments. Each chapter explores distinct structural modifications and functionalities of various Nap conjugates, investigating their photophysical behaviours, self-assembly properties, and interactions with biological targets (i.e. cell organelles). Each conjugate offers distinct advantages: triphenylamine (TPA) functionalised molecules enhance charge-transfer and red-shift the fluorescence for improved imaging, sugars enhance biocompatibility and facilitate enzyme-targeted applications, peptides provide selective cell-targeting capabilities and peptide gelators introduce self-assembling properties suited for fluorescent scaffold formation. Together, these modifications optimise the versatility of Naps in biomedical applications, including high-contrast imaging and therapeutic monitoring.
APPROVED
Keywords: Naphthalimides, bioimaging, fluorophores, medicinal chemistry, targeting drugs